E-064 Differential response of atrial fibrillation associated stroke with thrombolysis and mechanical thrombectomy. (4th August 2020) - Akbik, F; Alawieh, A; Cawley, C; Howard, B; Tong, F; Nahab, F; Samuels, O; Maier, I; Feng, W; Goyal, N; Starke, R; Rai, A; et al.
Abstract : Introduction: Atrial fibrillation (AF) associated stroke is associated with worse functional outcomes, less effective recanalization, and increased rates of hemorrhagic complications after intravenous thrombolysis (IVT). It remains unclear whether recanalization efficacy, procedural speed, and hemorrhagic complications differ in AF associated stroke treated with mechanical thrombectomy (MT). Methods: In a retrospective multicenter study of 4, 232 patients who underwent MT, 3, 385 patients had anterior circulation large vessel occlusions (LVO). 1, 210 (35.7%) patients had comorbid AF, diagnosed either before or on presentation. Baseline characteristics, procedural outcomes, and clinical outcomes were reported and compared. Results: AF was associated with faster procedural time (51.5 vs. 58.2 minutes, p=0.007), higher rates of first pass success (42% vs. 35%, p=0.001), and comparable angiographic outcomes. In multivariate analysis, AF was an independent predictor of both procedural speed and first pass success. AF patients had worse functional outcomes, attributable to increased age and stroke severity at presentation. In contrast to IVT associated sICH in AF patients, there was no additive risk of sICH after MT (aOR 0.95, 0.65–1.38, p=0.791). When patients who received IVT-MT were dichotomized by reperfusion status, only patients with poor reperfusion trended towards increased rates of sICH (aOR=2.69, 0.96 – 7.53, p=0.06). Conclusions: MT in AF patients is associated with increased rates of rapid reperfusion without added risk of sICH when reperfusion is achieved. Even when combined with IVT, MT in AF patients does not carry an added risk of sICH if successful recanalization is achieved. Given the historically low recanalization efficacy of IVT for AF associated stroke, it is unclear whether IVT is additive in the setting of AF associated LVO undergoing MT, particularly given the trend towards increased sICH if combined IVT-MT therapy ends with poor reperfusion. Randomized studies are warranted to evaluate whether AF patients with acute LVO may represent a subgroup of patients who may benefit from MT alone versus combined IVT-MT in thrombectomy capable centers. Disclosures: F. Akbik: None. A. Alawieh: None. C. Cawley: None. B. Howard: None. F. Tong: None. F. Nahab: None. O. Samuels: None. I. Maier: None. W. Feng: None. N. Goyal: None. R. Starke: None. A. Rai: None. K. Fargen: None. M. Anadani: None. M. Psychogios: None. R. De Leacy: None. S. Keyrouz: None. T. Dumont: None. P. Kan: None. J. Lena: None. J. Liman: None. A. Arthur: None. L. Elijovich: None. D. Mccarthy: None. V. Saini: None. S. Wolfe: None. J. Mocco: None. J. T Fifi: None. F. Nascimento: None. J. Giles: None. R. Crosa: None. W. Fox: None. B. Gory: None. A. Spiotta: None. J. Grossberg: None.